Control of the nanosized defect network in superconducting thin films by target grain size - Aye Moe Moe; Rivasto Elmeri; Khan Mukarram Zaman; Rijckaert Hannes; Salojärvi Esko; Haalisto Christopher; Mäkilä Ermei; Palonen Heikki; Huhtinen Hannu; Van Driessche Isabel; Paturi Petriina (NATURE RESEARCH, 2022)
A nanograined YBCO target, where a great number of grain boundaries, pores etc. exist, is shown to hold an alternative approach to future pulsed laser deposition based high-temperature superconductor thin film and coated conductor technologies. Although the nanograined material is introduced earlier, in this work, we comprehensively demonstrate the modified ablation process, together with unconventional nucleation and growth mechanisms that produces dramatically enhanced flux pinning properties. The results can be generalized to other complex magnetic oxides, where an increased number of defects are needed for modifying their magnetic and electrical properties, thus improving their usability in the future technological challenges.